Pengaruh Self Efficacy terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada PT. Aerofood ACS Denpasar: Studi Kasus Pada Departemen Kitchen - Kertiani, Ni Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
This study aims to determine self-efficacy and job satisfaction on employee performance as intervention variables in the Kitchen PT. Aerofood ACS Denpasar. Data collection methods used were observation, interviews, library research documents, and questionnaires. The research population is the number of employees in the kitchen of PT. Aerofood ACS Denpasar totaling 151 people, and the number of respondents using Slovin technology as many as 60 people. The data analysis technique used is path analysis. Based on the research results, it can be seen that: Self-efficacy (X) has a positive and significant effect on employee performance (Y). Self Efficacy (X) on job satisfaction (M) has a positive and significant impact. Job satisfaction (M) has a positive and significant impact on employee performance (Y). Job satisfaction (M) as an intervening variable that mediates Self Efficacy (X) on employee performance (Y) so that job satisfaction (M) has an impact on mediating Self Efficacy (X) on Employee Performance (Y), Kitchen Department PT. Aerofood ACS Denpasar.